An eco-epidemiological approach to management of tuberculosis in free-ranging and captive wildlife - Rosen, Laura Elizabeth, author; Olea-Popelka, Francisco J., advisor; Miller, Michele A., committee member; Huyvaert, Kathryn P., committee member; Hobbs, N. Thompson, committee member (Colorado State University. Libraries, 2018)
Tuberculosis (TB) is a disease of global importance affecting millions of humans, livestock, and wildlife. Control and eventual eradication of TB depends on dedicated management actions for all species. Accurately diagnosing TB can be challenging in wildlife species, for which validated tests may be unavailable or of limited sensitivity or specificity. Managing TB in wildlife poses additional difficulties, requiring considerable time and resources to implement at an appropriately broad scale. Each unique ecosystem where TB occurs requires management interventions designed to meet the area's conservation, ecological, social, and financial needs. In this dissertation, I explored the diagnosis and management of tuberculosis in wildlife in three different settings: free-ranging European badgers (Meles meles) in Ireland, working African elephants (Loxodonta africana) in Zimbabwe, and captive African and Asian elephants (Elephas maximus) in North America. Badgers are a reservoir of bovine TB in Ireland, while captive elephants around the world are at risk of TB from their human handlers. Badgers have historically been managed by culling, but there is a current transitioning to vaccination as the primary management tool. In contrast, captive elephants in high-resource settings are typically treated for TB upon diagnosis, although this option may be limited in low-income countries. The first objective of this research was to assess the impact of environmental factors in management of TB over three different studies. I explored how biotic and abiotic factors influence trapping success of badgers being managed for bovine TB in Ireland. In a second study of badgers, I estimated density of a population undergoing vaccination in relation to environmental variables and prior management history. Underlying badger density is an important driver in the TB disease dynamics between cattle and badgers, and can be used in predictions about and assessment of outcomes under vaccination. Finally, I examined potential risk factors for TB seropositive status in working African elephants in Zimbabwe, and identified unique potential exposures from the environment. The second objective of this dissertation was to study the performance of diagnostic tests in a novel setting and interpret the results in the context of exposures within the ecosystem. This study employed two serological tests, STAT-PAK and DPP, for the first time in working African elephants in a range country. I interpreted the results suggestive of exposure to mycobacteria in some elephants based on possible interactions with the complex community of humans, livestock, wildlife, and mycobacteria. The third objective of this dissertation was to develop recommendations for TB management programs based on surveys, capture data, and consideration of individual, population, and community factors. The results from our badger trapping study in Ireland formed the basis of suggested conditions under which vaccine delivery can be increased, because captures are most likely. We used mark-recapture data to estimate badger density in a vaccination area, which adds an important dimension to the Irish TB management program that includes badgers and cattle. Population density is an important factor in pathogen transmission and estimating density using these methods may be a priority for other wildlife populations being managed for TB. Our study of TB treatment in elephants provided a compilation of empirical data for elephant managers and veterinarians to inform clinical decision making. It also underscores the need for improved diagnostics to more confidently identify when animals are no longer infectious. For working African elephants, we documented other wildlife species with host potential on and around facilities, and considered these as possible sources for mycobacterial transmission. Our management guidelines for TB prevention specifically include measures to reduce direct and indirect contact with potential host species. Management of TB across humans and animal species remains a challenging prospect. A One Health approach that incorporates data and techniques across disciplines to build a complete picture of disease control is ideal for TB in wildlife. I drew from ecology and epidemiology to implement a holistic approach to diagnosing and managing TB in species of conservation concern, provide insight into the challenges of diagnosing and managing TB in free-ranging and captive wildlife, describe the benefits of a transdisciplinary approach, and expose areas in need of further research.
Keywords: elephant; tuberculosis; Zimbabwe; badger; wildlife management; Ireland